Osteoprotegerin, Soluble Receptor Activator of Nuclear Factor-κB Ligand, and Subclinical Atherosclerosis in Children and Adolescents with Type 1 Diabetes Mellitus - Irene Lambrinoudaki; Emmanouil Tsouvalas; Marina Vakaki; George Kaparos; Kimon Stamatelopoulos; Areti Augoulea; Paraskevi Pliatsika; Andreas Alexandrou; Maria Creatsa; Kyriaki Karavanaki (International Journal of Endocrinology)
Aims. To evaluate carotid intima-media thickness (cIMT) and biomarkers of the osteoprotegerin/receptor activator of nuclear factor-κB ligand (OPG/RANKL) system in type 1 diabetes (T1DM) children and adolescents and controls. Subjects and Methods. Fifty six T1DM patients (mean ± SD age: 12.0 ± 2.7 years, diabetes duration: 5.42 ± 2.87 years and HbA1c: 8.0 ± 1.5%) and 28 healthy matched controls, were studied with anthropometric and laboratory measurements, including serum OPG, soluble RANKL (sRANKL) and cIMT. Results. Anthropometric, laboratory, and cIMT measurements were similar between T1DM youngsters and controls. However patients with longer diabetes duration (>/7.0 years) had indicatively higher cIMT (cIMT = 0.49 vs 0.44 mm, P 0.072) and triglyceride levels than the rest of the patients (93.7 vs 64.6 mg/dl, P 0.025). Both in the total study population (β 0.418, P 0.027) and among T1DM patients separately (β 0.604, P 0.013), BMI was the only factor associated with cIMT. BMI was further associated with OPG in both groups (β −0.335, P 0.003 and β −0.356, P 0.008 respectively), while sRANKL levels were not associated with any factor. Conclusions. BMI was the strongest independent predictor of cIMT among the whole population, and especially in diabetics, suggesting a possible synergistic effect of diabetes and adiposity on atherosclerotic burden. BMI was overall strongly associated with circulating OPG, but the causes of this association remain unclear.